The influencing mechanism of big data analytics technology capability on enterprise's operational performance: The mediating role of data-tool fit - Huang, Xiangmeng; Yang, Shuai; Wang, Junbin; Lin, Fengli; Jiang, Yunfei (Frontiers in Psychology, 2022)
With the development of network technology, enterprises face the explosive growth of data every day. Therefore, in order to fully mine the value of massive data, big data analysis (BDA) technology has become the key to develop the core competitiveness of enterprises. To explore how BDA technology capability will influence enterprise operation performance, on the basis of Dynamic Capabilities Theory and Resource-based Theory, this study proposes the key variables, including the connectivity, compatibility, and modularization of big data analysis technical capability, enterprise operational performance, and the fit between data and tools, to establish model and study the correlation between the variables.